A link built between society, institutions and the “Benicio Delfín Pérez” Urban Natural Reserve. Report of an extension experience in higher education (Cuadernos de Extensión Universitaria de la UNLPam, 2022)
“Benicio Delfín Pérez” Reserve is the only protected area in the north of La Pampa province. It is a space with biodiversity, important natural and cultural values of local interest. These ambits are established by the municipality in concordance with the country's national system of protected areas. From a University Extension Project of the UNLPam, it was proposed to create an Interactive Center to provide specific information, link society with the Reserve, and turn it, through different activities, in a place with environmental education, artistic and tourist interest, in addition to promoting the sense of belonging. Scientific, artistic and educational aspects were combined, even in the context of a pandemic. Based on this experience, we reflect about a transformative education where teaching practices and the extension project become an opportunity to generate forms of connection, accompaniment and education in the territory.
Keywords: protected areas; interactive center; environmental education; tourist interest; ocial bonding